2010
DOI: 10.1371/journal.pone.0015394
|View full text |Cite
|
Sign up to set email alerts
|

The Association of AMPK with ULK1 Regulates Autophagy

Abstract: Autophagy is a highly orchestrated intracellular bulk degradation process that is activated by various environmental stresses. The serine/threonine kinase ULK1, like its yeast homologue Atg1, is a key initiator of autophagy that is negatively regulated by the mTOR kinase. However, the molecular mechanism that controls the inhibitory effect of mTOR on ULK1-mediated autophagy is not fully understood. Here we identified AMPK, a central energy sensor, as a new ULK1-binding partner. We found that AMPK binds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
330
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(349 citation statements)
references
References 39 publications
15
330
3
1
Order By: Relevance
“…35,36 Thus, under certain cellular settings, mTORC1 inhibition and AMPK activation may cooperate to trigger autophagy. [36][37][38] Although future research is needed to completely clarify this point, our data suggest that this could be the mechanism by which cannabinoids trigger autophagy in HCC cells. To note, it has been recently described that mTOR signaling has a critical role in the pathogenesis of HCC and that mTOR inhibitors have antineoplastic activity in experimental models of HCC.…”
Section: Discussionmentioning
confidence: 82%
“…35,36 Thus, under certain cellular settings, mTORC1 inhibition and AMPK activation may cooperate to trigger autophagy. [36][37][38] Although future research is needed to completely clarify this point, our data suggest that this could be the mechanism by which cannabinoids trigger autophagy in HCC cells. To note, it has been recently described that mTOR signaling has a critical role in the pathogenesis of HCC and that mTOR inhibitors have antineoplastic activity in experimental models of HCC.…”
Section: Discussionmentioning
confidence: 82%
“…[60][61][62] Moreover, direct physical interaction between AMPK or MTOR and ULK1 (unc-51 like autophagy activating kinase 1) plays a crucial role in the regulation of mammalian autophagy. [63][64][65][66][67][68][69] Under conditions of nutrients abundance, the activated MTOR phosphorylates ULK1 and prevents its interaction with AMPK. Conversely, under starvation conditions, AMPK-induced MTOR inhibition prevents MTOR from binding to ULK1.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…4B). The reason that Med1 was not labeled in the absence of AICAR in hepatocytes may be insufficient levels of active AMPK, as studies have shown that AMPK needs to be phosphorylated at its ␣-subunit by upstream kinases before it phosphorylates the substrates (32,43). Med1 phosphorylation was also observed in HeLa cells (data not shown).…”
Section: Ampk Forms a Complex With Med1 In Vivo And Binds Directly Tomentioning
confidence: 92%
“…The generation of other GST fusion fragments used in this study, such as PPARbinding protein (PBP/Med1)-(1-6), and the full-length mouse Med1 containing a His tag at the N terminus and cloned into pShuttle-CMV vector (pShuttle-His-Med1) have been described previously (25). FLAG-AMPK␣ plasmid was a kind gift from Dr. Hong-Gang Wang (Penn State College of Medicine, Hershey, PA) (43). Anti-Med1 (sc-8998) and anti-His (sc-803) were from Santa Cruz Biotechnology, Santa Cruz, CA.…”
Section: Methodsmentioning
confidence: 99%